PENGANEKARAGAMAN SAYURAN DI UD OMAH SAYUR SENGKALING UNTUK MENINGKATKAN PELAYANAN PENJUALAN DI DESA MULYOAGUNG, KECAMATAN DAU KABUPATEN MALANG - Purwanto; Zainol Arifin; Cakti Indra Gunawan; Cahyo Sasmito; Ida Sugeng Suyani (JURNAL DAYA-MAS, 2024)
"UD Omah Sayur" is a company that markets various kinds of horticultural vegetables and staple foods, such as carrots, spinach, lettuce, onions, chilies, mustard greens, kale, and other vegetables. Starting from being an employee in someone's factory, then leaving and opening his own business, called Omah Sayur."  is Mr. Nur Abdhiza. As the owner of the "UD Omah Sayur started developing "Omah Sayur" and played a direct role as the owner, while the others played roles as employees marketing the vegetables. Promotional media using the Internet is currently very relevant because people are used to looking for personal, company, or agency needs using Internet media. Surveys prove that 50% of home businesses or small and medium businesses already use the Internet as a promotional medium.